ANALYSIS OF ACCOUNTING INFORMATION SYSTEM AND MANAGEMENT CONTROL ON SALES EFFECTIVENESS AT KARISMA BRANCH MARVELL CITY MALL - Addin Islam Alfarizi; Herlambang Pudjo Santosa (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to examine the effect of Accounting Information Systems and management control on the effectiveness of sales at the Karisma Bookstore, Marvell City Mall branch. The sampling technique used in this study was a saturated sampling research technique, which is a sampling technique when all members of the population are used as samples. this saturation is a census. Where all members of the population are sampled. The sample used is 32 employees. The type of data used in this study is primary data, namely the main data taken directly from questionnaires filled out by respondents. And also Secondary Data, is data obtained from archives, documents, or records from the company, such as company history, company description, organizational structure, and others. The variables used are Accounting Information Systems and Management Control as independent. While the independent variable is Sales Effectiveness. And the research method used in this research is Multiple Linear Regression. The results of the study indicate that the Accounting Information System has no effect on Sales Effectiveness. While Management Control has an influence on the effectiveness of sales.